Biomarker discovery of nasopharyngeal carcinoma by proteomics. (April 2014) - Xiao, Liang; Xiao, Ta; Wang, Zhi-Ming; Cho, William CS; Xiao, Zhi-Qiang
<x xml:space="preserve">Abstract</x> Nasopharyngeal carcinoma (NPC) is one of the most common malignant tumors in southern China and southern Asia, and poses one of the most serious public health problems in these areas. Early diagnosis, predicting metastasis, recurrence, prognosis and therapeutic response of NPC remain a challenge. Discovery of diagnostic and predictive biomarkers is an ideal way to achieve these objectives. Proteomics has great potential in identifying cancer biomarkers. Comparative proteomics has identified a large number of potential biomarkers associated with NPC, although the clinical performance of such biomarkers needs to be further validated. In this article, we review the latest discovery and progress of biomarkers for early diagnosis, predicting metastasis, recurrence, prognosis and therapeutic response of NPC, inform the readers of the current status of proteomics-based NPC biomarker findings and suggest avenues for future work.